2009
DOI: 10.1179/acb.2009.071
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of Multiple Myeloma and Idiopathic Erythrocytosis

Abstract: The association of erythrocytosis and multiple myeloma is rare. We encountered a 76-year-old male patient with erythrocytosis followed by the diagnosis of multiple myeloma 8 months later. Related laboratory examinations revealed absolute erythrocytosis, normal oxygen saturation and erythropoietin (EPO) levels, the absence of endogenous erythroid colony (EEC) and JAK2-V617F mutations. The diagnosis of idiopathic erythrocytosis (IE), instead of polycythemic vera (PV), was made. In the literature, about 20 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…The study also reported that IgG-λ-type paraprotein and λ-light chains were identified in four and nine of the 11 previously reported cases of CNL associated with MM, respectively (4). In CML patients with concurrent MM, IgG-κ-type monoclonal paraprotein was predominant in the reported cases (9). In the present case, the patient was confirmed as λ-type by immunofixation electrophoresis, identical to the main type (λ-type) of CNL concurrent with MM.…”
Section: Discussionsupporting
confidence: 58%
“…The study also reported that IgG-λ-type paraprotein and λ-light chains were identified in four and nine of the 11 previously reported cases of CNL associated with MM, respectively (4). In CML patients with concurrent MM, IgG-κ-type monoclonal paraprotein was predominant in the reported cases (9). In the present case, the patient was confirmed as λ-type by immunofixation electrophoresis, identical to the main type (λ-type) of CNL concurrent with MM.…”
Section: Discussionsupporting
confidence: 58%
“…However, such a hypothesis is still unclear due to the lack of data on JAK2 V617F mutation; instead of this point of view, we considered that secondary or idiopathic erythrocytosis might be present in the early clinical course of PCM. In addition, unlike previous cases of secondary or idiopathic erythrocytosis where erythrocytosis has been found before PCM [2,4] , erythrocytosis and PCM were detected simultaneously in our case. Because it is known that the mass impinging on the kidney induces increased renal production of EPO as a result of increased pressure or local hypoxia within the kidney [13] , subclinical renal damage by Bence Jones protein in PCM could be one possible cause of coexisting PCM and erythrocytosis.…”
mentioning
confidence: 42%
“…To our knowledge, 18 cases of erythrocytosis associated with PCM were previously described in the literature [2][3][4][5][6][7][8][9][10][11] . Among these, 14 cases were diagnosed with polycythemia vera (PV), 2 cases with questionable secondary erythrocytosis, 1 case with secondary erythrocytosis, and 1 case with idiopathic erythrocytosis ( table 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, only four patients with otherwise unexplained polycythaemia and myeloma have been reported (table 1). 10 15–18 In three of those patients, polycythaemia preceded the diagnosis of myeloma by 8 months to 8 years 10 15 16. Only one patient had the concomitant diagnoses of polycythaemia of unknown aetiology and myeloma, as was the case with the patient described in our report.…”
Section: Discussionmentioning
confidence: 49%